2021
DOI: 10.3846/btp.2021.13365
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Proactive Knowledge Sharing Among Transformational Leadership, Cohesion, and Learning Goal Orientation on Employee Performance

Abstract: The background of this study is based on the controversial relationship between transformational leadership and employee performance. Empirical and theoretical models resolve the controversy by building a new concept based on proactive knowledge sharing. The study established the influence of transformational leadership, cohesion and learning goal orientation on proactive knowledge sharing and employee performance. A total of 7 hypotheses were developed to solve the study problem, while purposive sampling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
(83 reference statements)
1
8
0
1
Order By: Relevance
“…One leadership style that is adaptive to organizational performance is transformational leadership. This is in line with findings by Layaman et al (2021), ABSTRACT Leadership style is a complex phenomenon involving the leader, followers, and circumstances. The leadership style in an organization is also related to the overall success of the team.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…One leadership style that is adaptive to organizational performance is transformational leadership. This is in line with findings by Layaman et al (2021), ABSTRACT Leadership style is a complex phenomenon involving the leader, followers, and circumstances. The leadership style in an organization is also related to the overall success of the team.…”
Section: Introductionsupporting
confidence: 91%
“…According to Northouse (2016), Yucel (2021), andDonkor (2021), leadership and leadership style are key factors in organizational growth and success. Two styles of leadership were described in some writings: namely transformational leadership and transactional leadership (Yucel, 2021;Layaman et al, 2021;Tambakan et al, 2020;Aboramadan & Dahlesz, 2020;and Donkor, 2021). Burns (1978), a pioneer in the study of transformational leadership, said that transformational leadership can optimally transform the human resources of the organization to achieve a predetermined goal and target.…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%
“…Imam and Zaheer (2021) that a shared approach to leadership significantly imply the success of IT projects through the important role of cohesion and knowledge sharing. Similarly, Layaman et al (2021) found the role of transformational leadership on cohesion, learning goal orientation and employee performance among banking employees in Indonesia. Social Identity Theory explains that team membership builds a sense of team identity; that is, team members think more like a representative of the team than as an individual (Turner and Oakes, 1986).…”
Section: The Mediating Role Of Team Efficacy Cohesion Commitment and ...mentioning
confidence: 88%
“…The research of Buil et al (2019) uses two (2) mediating variables, namely identification and work engagement. While in the study of Layaman et al (2021) used a proactive knowledgesharing variable. The results show that these three (3) variables mediate the effect of leadership style on performance.…”
Section: B Has No Influencementioning
confidence: 99%